Novel mucosal immunization with polysaccharide-protein conjugates entrapped in alginate microspheres - Cho, NH; Seong, SY; Chun, KH; Kim, YH; Kwon, IC; Ahn, BY; Jeong, SY (ELSEVIER SCIENCE BV, 1998)
A novel mucosal immunization was examined using biocompatible and biodegradable alginate microspheres containing a conjugate of polysaccharide antigen and cholera toxin B subunit (CTB). In order to prepare the alginate microspheres with diameters of less than 5 mu m, a new diffusion-controlled interfacial gelation technique was developed. Also, in order to improve the mucosal immune response, a pneumococcal capsular polysaccharide type 19 (PS19) was conjugated to the CTB (PS19-CTB). This conjugate was subsequently encapsulated into the alginate microspheres. The loading content of PS19-CTB to the alginate microspheres was 60%. An in vitro sustained release pattern was observed with the antigen-loaded microspheres, showing 80% antigen release within one day. Mucosal and systemic immunities following oral immunization with the alginate microspheres were studied. Balb/c mice were immunized perorally three times at intervals of two weeks. Peroral immunization with 25 mu g of PS19-CTB entrapped in the alginate microspheres evoked both the mucosal IgA and systemic IgM responses to PS19 in small intestine and in sera, respectively. The results suggest that both the mucosal and systemic antibody responses could be induced by oral administration of the PS19-CTB antigen entrapped in alginate microspheres. (C) 1998 Elsevier Science B.V.
Keywords: PARTICLE-SIZE; POLY(LACTIDE-CO-GLYCOLIDE) MICROPARTICLES; DISPERSION POLYMERIZATION; CONTROLLED-RELEASE; SUPPRESSOR CELLS; PEYERS PATCHES; INDUCTION; RESPONSES; ANTIGEN; VACCINATION